Morphological changes of mammalian nucleoli during spermatogenesis and their possible role in the chromatoid body assembling - Peruquetti, Rita Luiza; Taboga, Sebastião Roberto [UNESP]; Oliveira, Maria Tercilia Vilela de Azeredo [UNESP] (Hindawi, 2012)
Chromatoid body (CB) is a typical cytoplasmic organelle of germ cells, and it seems to be involved in RNA/protein accumulation for later germ-cell differentiation. Despite most of the events in mammals spermatogenesis had been widely described in the past decades and the increase in the studies related to the CB molecular composition and physiology, the origins and functions of this important structure of male germ cells are still unclear. The aims of this study were to describe the nucleolar cycle and also to find some relationship between the nucleolar organization and the CB assembling during the spermatogenesis in mammals. Cytochemical and cytogenetics analysis showed nucleolar fragmentation in post-pachytene spermatocytes and nucleolar reorganization in post-meiotic spermatids. Significant difference in the number and in the size of nucleoli between spermatogonia and round spermatids, as well as differences in the nucleolar position within the nucleus were also observed. Ultrastructural analysis showed the CB assembling in the cytoplasm of primary spermatocytes and the nucleolar fragmentation occurring at the same time. In conclusion our results suggest that the CB may play important roles during the spermatogenesis process in mammals and that its origin may be related to the nucleolar cycle during the meiotic cell cycle.